PERSPEKTIF HUKUM ADAT KAWIN LARI (SILAYYANG) SUKU BAJAU DI DESA LA GASA KABUPATEN MUNA - Yaya Alfia; Suriani Bt Tolo; La Ode Munawir (Unissula, 2021)
This study aims to explain the legal perspective of the unregistered Kawin Lari (Silayyang) of the Bajau Tribe in Lagasa Village, Muna Regency which is contrary to Law no. 1/1974. This research is an empirical juridical research by combining legal materials (which are secondary data) with primary data obtained in the field. The results showed that Silayyang which is a marriage that is considered valid based on consensual, and with the existence of silayyang which is an alternative for young people to get married without having to be burdened with expensive costs, and is a marriage that is registered and gets legal legality. As a result, there are marriages that are registered according to the marriage law, but some are not. Marriages that are not registered according to the marriage law and the imposition of sanctions, namely the payment of a fine by paying an amount of money according to the customary rules that apply in the village that have been agreed upon. Basically, elopement is an act that violates the value of customary law, violates the power of parents, and destroys the honor of the dignity of the parents and relatives of the party being taken.Â Penelitian ini bertujuan untuk menjelaskan Perspektif Hukum Adat Kawin Lari (Silayyang) Suku Bajau di Desa Lagasa Kabupaten Muna yang tidak tercatat yang bertentangan dengan UU No. 1/1974. Penelitian ini adalah penelitian yuridis empiris dengan Â menggabungkan bahan-bahan hukum (yang merupakan data sekunder) dengan data primer yang diperoleh di lapangan. Hasil penelitian menunjukan bahwa kawin lari (silayyang) merupakan perkawinan yang Â dianggap sah berdasarkan suka sama suka, dan dengan adanya silayyang merupakan alternatif bagi kalangan muda mudi untuk melakukan perkawinan tanpa harus terbebani dengan biaya yang mahal dan merupakan perkawinan tercatat dan mendapatkan legalitas hukum. Dampaknya ada perkawinan yang tercatat sesuai dengan undang-undang perkawinan namun ada pula yang tidak tercatat. Perkawinan yang tidak tercatat sesuai undang-undang perkawinan serta pemberian sanksi yaitu pembayaran denda dengan membayar sejumlah uang sesuai aturan adat yang berlaku di desa yang telah disepakati. Pada dasarnya kawin lari merupakan salah satu tindakan yang melanggar nilai hukum adat, melanggar kekuasaan orang tua, dan menjatuhkan kehormatan martabat orang tua dan kerabat dari pihak yang dilarikan.